500 tips for primary teachers - Packar, Emma.; Packard, Nick.; Brown, Sally (USA : Kogan page, 1997)
This manual provides practical advice and tips on dealing with aspects of the primary teacher's role, from classroom organization to professional development.
Includes index.
Keywords: Early childhood teachers; Preschool teaching; Education, Preschool